Modification of Rice Straw Cellulose with Acrylamide using Ammonium Persulfate Initiator by Microwave Assisted - Sperisa Distantina; Insan Idealina Citra; Putu Amelia Indira Putri; Kaavessina Mujtahid (Jurnal Teknik Kimia dan Lingkungan, 2026)
In this study, rice straw powder was grafted with acrylamide (AA) using amonium persulfate (APS) as an initiator to obtaine rice straw cellulose-graft-polyacrylamide (RS-g-PAA). The resulting RS-g-PAA was then mixed with carrageenan to form bead gel. This research aimed to determine the influence of the amount of acrylamide and ammonium persulfate as an initiator on the swelling capacity of bead gels. The mixture of 1 g of rice straw cellulose, AA (5, 10, 15 g), APS (0.05, 0.10, 0.15 g), and 50 mL aquadest was irradiated using microwave at 540 W for 30 s with cooling cycles. The aqueous mixture of RS-g-PAA and carrageenan was injected into palm oil layer and then crosslinked using KCl and CaCl₂. The results of FTIR show that the successful grafting by the appearance of amide groups in the RS-g-PAA structure. The bead gel with 15 g AA showed the highest swelling capacity of 1806.12% in aquadest and 1611.58% in urine solution. Bead gels from APS of 0.10 g produced the highest swelling capacity of 1218.15% in aquadest and 975.20% in urine solution. Therefore, the bead gels based on RS-g-PAA and carrageenan demonstrate strong potential as an environmentally friendly superabsorbent polymers.